Formulasi dan Karakterisasi Fitosom Ekstrak Biji Buah Makasar (Brucea Javanica (L) Merr) dengan Metode Pembuatan Hidrasi Lapis Tipis: Formulation and Characterization of Phytosome Extract Makassar Fruit Seeds (Brucea Javanica (L) Merr) with the Method of Manufacturing Thin Layer Hydration - Nur Amalina Sabdarrifa; Windah Anugrah Subaidah; Sucilawaty Ridwan; Wahida Hajrin (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2025)
Brucea javanica seeds hold promise as a powerful antioxidant source, boasting a high phenol content (61.1927±0.1560 mg GAE/g sample) and an IC50 value of 64,703 ppm. However, the inherent polar and bulky nature of these phenols limits their absorption in the body, hindering their effectiveness. This research introduces phytosomes, a potential solution, derived from Brucea javanica seed extract. The phytosomes are prepared using sonication and thin-film hydration techniques, with optimized parameters for phospholipid concentration, processing speed, and rotary evaporator temperature. Different ratios of phospholipid to Brucea javanica extract (1:1, 1:2, 1:3, and 2:1) are evaluated to determine the optimal phytosome formulation. Encapsulation efficiency serves as the primary parameter for selection. Finally, the most promising phytosome is characterized for particle size, polydispersity index, vesicle morphology, and the complexity of the formed compounds using infrared spectroscopy. This study strives to develop an optimal phytosome formulation from Brucea javanica seeds with superior absorption, aiming to enhance the antioxidant's pharmacological effects and open new avenues in the healthcare field. Keywords: Brucea javanica, antioxidants, phenols, phytosomes, hydration of thin films Abstrak Biji Brucea javanica kaya fenol (61,1927±0,1560 mg GAE/g sampel) dengan nilai IC50 64,703 ppm. Sifat polar dan bermolekul besar fenol menghambat absorpsinya. Penelitian ini menghadirkan fitosom dari ekstrak biji Brucea javanica untuk meningkatkan absorpsi. Fitosom diolah dengan metode sonikasi dan hidrasi lapis tipis, dengan optimasi konsentrasi fosfolipid, kecepatan, dan suhu rotary evaporator. Berbagai perbandingan fosfolipid dan ekstrak Brucea javanica (1:1, 1:2, 1:3, dan 2:1) dievaluasi untuk menentukan formula fitosom terbaik. Efisiensi penjerapan menjadi parameter utama. Fitosom dengan formula terbaik dikarakterisasi untuk mengetahui ukuran partikel, indeks polidispersitas, morfologi vesikel, dan kompleksitasnya dengan spektroskopi inframerah. Penelitian ini diharapkan menghasilkan formulasi fitosom optimal dari biji Brucea javanica dengan daya serap tinggi, meningkatkan efek farmakologisnya, dan membuka peluang baru di bidang kesehatan. Kata Kunci: Brucea javanica, antioksidan, fenol, fitosom, hidrasi lapis tipis